1986
DOI: 10.1083/jcb.102.6.2147
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic domains of cellular and viral integral membrane proteins substitute for the cytoplasmic domain of the vesicular stomatitis virus glycoprotein in transport to the plasma membrane.

Abstract: Abstract. Oligonucleotide-directed mutagenesis was used to construct chimeric cDNAs that encode the extracellular and transmembrane domains of the vesicular stomatitis virus glycoprotein (G) linked to the cytoplasmic domain of either the immunoglobulin u membrane heavy chain, the hemagglutinin glycoprotein of influenza virus, or the small glycoprotein (023) of infectious bronchitis virus. Biochemical analyses and immunofluorescence microscopy demonstrated that these hybrid genes were correctly expressed in euk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 66 publications
3
43
0
Order By: Relevance
“…2). Mutant 1473 is completely inhibited in transport, only 10% of TMS is transported after 2 h, and GIx, TMR, and GHA are transported efficiently but four-to eightfold more slowly than wt G protein (Puddington et al, 1986). The results showed that trimerization alone is not sufficient for transport.…”
Section: Mutant Proteins With Alterations In the Cytoplasmic Domainmentioning
confidence: 60%
See 3 more Smart Citations
“…2). Mutant 1473 is completely inhibited in transport, only 10% of TMS is transported after 2 h, and GIx, TMR, and GHA are transported efficiently but four-to eightfold more slowly than wt G protein (Puddington et al, 1986). The results showed that trimerization alone is not sufficient for transport.…”
Section: Mutant Proteins With Alterations In the Cytoplasmic Domainmentioning
confidence: 60%
“…This group of mutants had alterations in the cytoplasmic domain. Mutant 1473 was completely blocked in transport, only 10% of TMS was transported after 2 h, while GHA, G~t, and TMR were transported efficiently but at one-fourth to one-eighth the wt rate (Puddington et al, 1986). The mutants acquired all the antigenic epitopes characteristic of the mature G protein and, with the exception of TMS, they trimerized with wt kinetics.…”
Section: Transport-defective Trimersmentioning
confidence: 91%
See 2 more Smart Citations
“…In these studies, deletions or substitutions of amino acids were made in cytoplasmic domains of several proteins. In some cases dramatic decreases in rates of transport or blocks in transport were observed, while in other cases the effect was minimal (2,11,18,20,21,25). One simple way to reconcile all of these results is to say that when an effect on transport is observed, it is due to an indirect effect on oligomerization or folding of the ectodomain of the protein and not directly related to interactions on the cytoplasmic side.…”
mentioning
confidence: 87%